Perceptions of Adult Women on Losing Their Mothers at an Early Age: Implications for Nursing Care During Childbirth. Issue 3 (May 2018) - Gunn, Jennie; Huebner, Carroll Gunn; McCoy, Kristen
Abstract: Purpose: To explore the lived experience of women over the age of 21 who lost their mothers before the age of 18. Methods: Using qualitative methodology, motherless child–adult women were gathered through emails, word of mouth, and snowballing techniques. Interviews were conducted at the convenience of the women. The women coparticipated with identification of emerging themes using thematic analysis. Results: Eight women who lost their mothers before the age of 18 participated. Eight themes emerged: (1) Understanding: For wounded hearts only; (2) Coming apart: Finding my mother's daughter and self-worth; (3) Unconditional love: Grieving for and identifying with my champion; (4) Finding help: Filling the empty place with God; (5) Pitying the motherless child: Making it worse; (6) Filling in: Others as mother; (7) The ebb and flow: Grieving; and (8) Becoming mother: Taking on the Role. Clinical Implications: The nurse has the opportunity to improve care for women who lost their mothers before the age of 18 years. During pregnancy, childbirth, and childrearing, the woman may feel sad and anxious without the guidance of her mother. Special ways of caring may be instituted to provide her comfort such as allowing and encouraging her to bring a special item of her mother's to procedures and events so that she may feel connected with her, allowing someone to stand in for her mother, perhaps assisting in finding of another motherless child adult to be with her as needed, and the voicing of understanding of her loss while remaining nonjudgmental about her emotions during these times. Abstract : Loss of mother during childhood can be a devastating blow to the child, with multiple implications that last a lifetime. In this study, adult women who lost their mother during childhood share their perceptions of how this loss has affected many aspects of their life. The researchers offer suggestions for incorporating the findings into nursing care of women in this unique group during the childbirth process.